2018
DOI: 10.1007/978-3-030-02671-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Highly Scalable Object-Aware Process Management Engine Using Distributed Microservices

Abstract: Scalability of information systems has been a research topic for many years and is as relevant as ever with the dramatic increases in digitization of business processes and data. This also applies to processaware information systems, most of which are currently incapable of scaling horizontally, i.e., over multiple servers. This paper presents the design science artifact that resulted from engineering a highly scalable process management system relying on the object-aware process management paradigm. The latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…In [53], the authors present a highly scalable objectaware process management engine that is using distributed microservices on cloud resources. As an underlying architecture, the authors are using the actor model, where each microservice is an actor (comparable to our services) and connected to different other actors according to a data model.…”
Section: Related Workmentioning
confidence: 99%
“…In [53], the authors present a highly scalable objectaware process management engine that is using distributed microservices on cloud resources. As an underlying architecture, the authors are using the actor model, where each microservice is an actor (comparable to our services) and connected to different other actors according to a data model.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, for object-aware process management, distributed process coordination is of particular importance, as the run-time engine of object-aware process management has a hyperscale architecture [2]. The term hyperscale denotes the ability of the process engine to effectively scale with additionally provisioned resources to provide more performance when computing demands are increasing.…”
Section: Solution Approachmentioning
confidence: 99%
“…First, it is shown that the decentralization of coordination constraints over multiple coordination processes not only has conceptual benefits for modelers. The decentralization also enables significant performance increases in a hyperscale architecture [2]. A corresponding experiment with the goal of showcasing this performance advantage has been performed.…”
Section: A Proof-of-concept Prototype and A Validation Whichmentioning
confidence: 99%
See 2 more Smart Citations